THE PSYCHOLOGICAL CONFLICT OF THE MAIN CHARACTER IN “GONE GIRL NOVEL” BY GILLIAN FLYNN - Situmorang, Dina Evianna; Arianto, Tomi (LPPM Universitas Putera Batam, 2022)
This study aimed to analyze the psychological conflict of the main character in the novel Gone Girl by Gillian Flynn. The main character of this novel is Amy. In conducting this research, the researchers used Sigmund Freud's theory.In his theory, Freud introduced the structure of the human personality into three, namely the id, ego, and superego. In a person's personality, these three structures will rage to highlight their dominance and give birth to an action. This study limits itself to the disclosure of the dominance of the id and the impact of this dominance on the main character. In analyzing this research, the researcher used a qualitative descriptive method. The results of this study indicate that the dominant id in Amy's personality is shown through attitudes including committing murder without guilt to achieve her goals. There is satisfaction in him having made his parents worry about him and Amy's act of lying to the media. The impact of personality that puts forward the structure of the id include: someone becomes a murderer, a liar and even steals.